Constituting Child-to-Parent Violence: Lessons from England and Wales - Holt, Amanda (The British journal of criminology, 2021)
This paper draws upon the first national study of local responses to child-to-parent violence (CPV) in England and Wales to examine emergent representations of CPV and consider their implications for children and families. Central amongst these is the Government’s depiction of CPV as a form of ‘domestic violence and abuse’. For many individuals and organizations, that term is synonymous with intimate partner violence. We contend that the resulting conflation of (and confusion between) violence by intimate partners, and by children, towards women is producing dominant representations of CPV that may have negative consequences for families. Our research with over 200 practitioners reveals the existence of subjugated knowledges of CPV, however, that provide pockets of resistance to these dominant representations.